Efficient Transmitter and Receiver Designs for SC-FDMA Based Heterogeneous Networks Castanheira, D. ; Silva, A. ; Dinis, R. ; Gameiro, A. - Dinis, Rui (2018)
In this manuscript, we consider the uplink of a single carrier frequency division multiple access (SC-FDMA) based system, where a set of small-cells coexist with a macro-cell using the same spectrum. To deal with both the inter-carrier interference (ICI) and inter-system interference we combine interference alignment (IA) precoding at the small-cell transmitters with iterative decision feedback equalization at the macroreceiver. The transmitter and receiver design is performed jointly, by considering both full-coordination and limited inter-system information exchange between macro and small-cells. At the small cells side, we assume that the access points are connected through a limited capacity backhaul network to a central unit, where the separation of a quantized version of the small-cell signals is performed. For this case the iterative feedback equalizer is designed by explicitly taking into account the impact of signal quantization. Moreover, a semi-analytical approach for the performance of the proposed schemes is provided. The results show that the proposed schemes are robust to both inter-system and inter-carrier interferences and thus are able to efficiently separate the macro and small cells spatial streams under limited information exchange.